3D printed ceramic vault shading systems - Carvalho, João (2018)
The emergence and dissemination of additive manufacturing technologies, namely three-dimensional printing, contributes to a paradigm shift in the process of project design and construction by allowing these two traditionally autonomous phases to approach. The use of digital manufacturing technologies has considerably expanded the formal, performative, and functional limits that ceramic elements can bring to the context of construction and architecture. This paper presents the main challenges and outcomes achieved during the process of design and production of a vault cover system. Based on the discretization of a vault in hexagonal blocks, this system intends to control solar incidence by its adaptive inner structure. It focuses on objective questions like material composition, ceramic material retraction and the influence that geometry variations have on those themes. These questions try to evaluate the real applicability of digital additive manufacturing techniques, specifically ceramic 3D printing on architecture and design production processes.